Identifikasi Produk Bahan Obat Berbahan Dasar Alga (Mikro Alga atau Makroalga) pada Pasar Tradisional/Modern di Kota Medan - Ulfah, Syarifah Widya; Mawaddah, Hanifa; Lubis, Isnaini Rahma; Lubis, Muhammad Fazil Mawla; Amalia, Qoyum (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Algae has the potential to be a very useful resource for humans. Some types of algae are known to have antioxidant, anticancer, anti-inflammatory, and antifungal properties that can help in treating diseases. This research was conducted in traditional and modern markets in the city of Medan, especially in Jl. Jamin Ginting, North Sumatra. The aim of this research is to identify the types of medicinal products made from algae (microalgae or macroalgae) available in traditional/modern markets in the city of Medan. The sampling method used was cruise methods with Purposive Sampling Technique. The results of the research show three types of medicinal products in traditional and modern markets in the city of Medan that are made from algae, namely Ever E 250 (Seaweed Capsules), Algae Calcium (Red Algae), and Brown Seaweed. Some health benefits of red algae include maintaining thyroid function, lowering cholesterol, and being a healthy diet option. The benefits of brown algae include algin or alginate acid from brown algae used in making ice cream, pills, ointments, toothpaste, and lotion. Meanwhile, green algae contains carotenoids, phycocyanin, plant sterols, and linoleic acid that can help maintain heart health.